2021
DOI: 10.1097/jcn.0000000000000865
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and the Relationship With Health Literacy and Secondary Prevention in Patients With Acute Coronary Syndrome at Early Discharge

Abstract: Background: Cognitive impairment (CI) may contribute to difficulties in understanding and implementing secondary prevention behavior change after acute coronary syndrome (ACS), but the association is poorly understood. Objectives: The aim of this study was to explore the prevalence of CI in patients 4 weeks post ACS and the association with health literacy and secondary prevention. Methods: Patients with ACS who were free from visual deficits, auditory impairment, and dementia diagnoses were recruited and asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…14 Although the MoCA is highly sensitive for vascular cognitive impairment, we used 2 cognitive screens because authors of previous studies have identified cases of MCI that would have gone undetected without the use of a second instrument. 10 This was replicated in this study with the MoCA failing to detect 3 of 81 positive HVLT screens (3.7%) and the HVLT failing to detect 31 of 81 (38.3%) of the positive MoCA screens, likely due to the MoCA testing several cognitive domains compared with the HVLT testing only new verbal learning. The prevalence of MCI has been identified in 28.9% at 4 weeks post ACS using 2 cognitive screens, and 62.5% single-domain and 22.5% multiple-domain MCI at cardiac rehabilitation entry using a battery of 5 neuropsychological tests.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…14 Although the MoCA is highly sensitive for vascular cognitive impairment, we used 2 cognitive screens because authors of previous studies have identified cases of MCI that would have gone undetected without the use of a second instrument. 10 This was replicated in this study with the MoCA failing to detect 3 of 81 positive HVLT screens (3.7%) and the HVLT failing to detect 31 of 81 (38.3%) of the positive MoCA screens, likely due to the MoCA testing several cognitive domains compared with the HVLT testing only new verbal learning. The prevalence of MCI has been identified in 28.9% at 4 weeks post ACS using 2 cognitive screens, and 62.5% single-domain and 22.5% multiple-domain MCI at cardiac rehabilitation entry using a battery of 5 neuropsychological tests.…”
Section: Discussionsupporting
confidence: 64%
“…The prevalence of MCI has been identified in 28.9% at 4 weeks post ACS using 2 cognitive screens, and 62.5% single-domain and 22.5% multiple-domain MCI at cardiac rehabilitation entry using a battery of 5 neuropsychological tests. 10,12 One for these high MCI rates in ACS could be the shared pathology and coexistence of vascular cognitive impairment and coronary heart disease. 7 Neurovascular dysfunction, increased blood-brain barrier permeability, and microvascular thrombosis are all mediated by endothelial damage, which is triggered by vascular risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations